Capturing structure and function in an embryonic heart with biophotonic tools - Karunamuni, Ganga H.; Gu, Shi; Ford, Matthew R.; Peterson, Lindsy M.; Ma, Pei; Wang, Yves T.; Rollins, Andrew M.; Jenkins, Michael W.; Watanabe, Michiko (Frontiers in Physiology, 2014)
Disturbed cardiac function at an early stage of development has been shown to correlate with cellular/molecular, structural as well as functional cardiac anomalies at later stages culminating in the congenital heart defects (CHDs) that present at birth. While our knowledge of cellular and molecular steps in cardiac development is growing rapidly, our understanding of the role of cardiovascular function in the embryo is still in an early phase. One reason for the scanty information in this area is that the tools to study early cardiac function are limited. Recently developed and adapted biophotonic tools may overcome some of the challenges of studying the tiny fragile beating heart. In this chapter, we describe and discuss our experience in developing and implementing biophotonic tools to study the role of function in heart development with emphasis on optical coherence tomography (OCT). OCT can be used for detailed structural and functional studies of the tubular and looping embryo heart under physiological conditions. The same heart can be rapidly and quantitatively phenotyped at early and again at later stages using OCT. When combined with other tools such as optical mapping (OM) and optical pacing (OP), OCT has the potential to reveal in spatial and temporal detail the biophysical changes that can impact mechanotransduction pathways. This information may provide better explanations for the etiology of the CHDs when interwoven with our understanding of morphogenesis and the molecular pathways that have been described to be involved. Future directions for advances in the creation and use of biophotonic tools are discussed.